Post-earthquake highway reconstruction: Impacts and mitigation opportunities for New Zealand pinniped population - Hall AA; Chilvers BL; Weir JS; Vidulich A; Godfrey AJR (Elsevier B.V., 2023)
Knowledge of how roads impact wildlife populations is limited but required to inform management and mitigation. Prioritising sites for mitigation involves identifying the most at-risk areas and populations, particularly after substantial changes to roading infrastructure. We identify hotspots for New Zealand fur seal (NZFS: Arctocephalus forsteri) incidents (live or dead NZFS) on State Highway 1 (SH1) around Kaikōura, on New Zealand's South Island, and analyse whether hotspot locations have persisted following earthquake-induced road reconstruction. We also assess spatial, environmental, and temporal influences of NZFS incidents. Spatial records of incidents along SH1 were analysed to identify contemporary and former hotspots using Kernel Density Estimation Plus and a Poisson-based method. Spatial, temporal and environmental data were collected to assess these factors’ effects on incident location and timing. Between 2012 and 2022, an average of 59 incidents were recorded annually along 90 km of SH1. Ten significant hotspots accounted for 89% of incidents, along 2.75 km of road. Hotspot concentration shifted following road reconstruction. Incident numbers were significantly positively associated with traffic volumes and windspeed, and significantly negatively associated with temperature and rainfall. Autumn experienced significantly more incidents than any other season. Road-abutting NZFS breeding areas explained most of the spatial variation in incidents. SH1 is a threat to Kaikōura's NZFS, with its effects changing following an earthquake impacting NZFS distribution, and associated highway reconstruction. Hotspot analysis and current road protections suggest the risks could be substantially reduced by barrier construction along short stretches of road. This type of assessment should continue as climate change raises sea levels and increases storm events globally. This analysis and mitigation approach could be used for any wildlife across numerous landscapes.
Keywords: Arctocephalus forsteri; Hotspot persistence analysis; New Zealand Fur seal; Roads